Crítica feminista a la penalización del aborto en casos de violación sexual: una mirada interseccional a propósito del embarazo infantil - Solís Peña, Victoria Natividad (2019)
This article analyzes the problem of the criminalization of abortion in cases of sexual rape from a critical feminist perspective. It emphasizes the differentiated impact that this discriminatory use of criminal law generates in girls under 14 years of age, regarding the increasingly alarming problem of child pregnancy in Peru and Latin America. Because of this, the author uses methodologies for analyzing the legal phenomenon proposed by feminisms, in the light of the principle of Higher Interest of the Child and international standards for the protection of children and gender equality, present in the International Human Rights Law.